The Emerging Applications of Nanotechnology in Neuroimaging: A Comprehensive Review - Faiz, Khunza; Lam, Fred C.; Chen, Jay; Kasper, Ekkehard M.; Salehi, Fateme (Frontiers in Bioengineering and Biotechnology, 2022)
Nanotechnology is an emerging field where engineered nanoparticles (NPs) are used for detection, treatment, and prevention of multiple neurological diseases. Magnetic particle imaging (MPI) is a tracer imaging technique with high spatial and temporal resolution that allows tracking and quantification of NPs. In the field of neuroimaging, MPI has shown promising applications in vascular and oncological imaging, cell tracking and multiple other neurological conditions including neurodegenerative diseases and epilepsy. In this review, we will highlight the applications of MPI in neuroimaging, briefly discuss the limitations in the use of NPs and explore the future implication of this emerging imaging modality.